1999
DOI: 10.3141/1659-04
|View full text |Cite
|
Sign up to set email alerts
|

Benefit-Cost Evaluation of the Electronic Toll Collection System: A Comprehensive Framework and Application

Abstract: Although electronic toll collection (ETC) technologies are fairly mature and many ETC systems have been implemented, there is a dearth of comprehensive and systematic assessment of their benefits and costs. Most previous studies have focused only on one or two short-term benefits or costs and have not translated the benefits into dollar values. A comprehensive framework is proposed, incorporating various benefit and cost components, and decomposing the benefits and costs by affected groups. The framework also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…This research followed standard practices used in the benefit-cost analysis of a transportation project (Federal Highway Administration, 2000;Li et al, 1999). Actual costs and benefits were used wherever possible.…”
Section: Benefit-cost Analysis Methodologymentioning
confidence: 99%
“…This research followed standard practices used in the benefit-cost analysis of a transportation project (Federal Highway Administration, 2000;Li et al, 1999). Actual costs and benefits were used wherever possible.…”
Section: Benefit-cost Analysis Methodologymentioning
confidence: 99%
“…Nonetheless, in practice the technology enabling the deployment of road pricing constitutes a critical and integral component of the overall scheme design. Moreover, current evaluation of road pricing schemes mostly ignores installation, operational (toll collection and enforcement) and maintenance costs, although it has been widely argued that the type of technology and its cost structure can significantly affect the decisions of road providers and users, and the economic appraisal of such schemes [117,217,220,294]. Traditional (surface) traffic surveillance systems, such as those of inductance loop detectors (passive sensors), have been used to estimate link-based congestion toll rates based on aggregate speed-flow relationships [218,219,413].…”
Section: Technological Advances For Deploying Road Network Pricing Scmentioning
confidence: 99%
“…Li et al proposed a comprehensive framework to implement the benefit-cost evaluation, the case study showed that the ETC project would generate a benefit-cost ratio of 40 over the entire evaluation period [5]. The major benefits of ETC system include time saving, energy saving, emission reduction, and service improvement.…”
Section: Literature Reviewmentioning
confidence: 99%